Gold investment behaviour among Muslim generational cohorts - Rizal, Achmad; Riza, Alex Fahrur; Asuhaimi, Fadhilah Abudullah; Susilo, Adib (Asian Journal of Islamic Management (AJIM), 2025)
Purpose – This study examines how financial attitude, behavior, knowledge, literacy, financial socialization, and subjective norms influence individuals’ intention to invest in gold across Generations X, Y, and Z. Grounded in Islamic Management principles, it positions gold as a Shariah-compliant asset aligned with ethical wealth creation and prudent risk management. This study contributes to Islamic wealth management by exploring how intergenerational dynamics shape ethical investment behavior.Methodology – A quantitative approach was employed using a structured questionnaire distributed to 360 respondents from three generations in Malaysia, with most participants being residents of Indonesia. The data collected were analyzed using partial least squares structural equation modeling (PLS-SEM)Findings – The results indicated that the measurement model met the recommended reliability and validity standards. Financial attitude, behavior, and knowledge positively enhance financial literacy, which, along with financial attitudes, financial knowledge, financial socialization, and subjective norms, significantly shape gold investment intention. Generational differences were evident: Gen Z’s intention was strongly driven by financial knowledge and social expectations; Gen Y was influenced mainly by financial attitude; and Gen X relied more on financial socialization and subjective norms. The overall model demonstrated strong predictive and explanatory power.Implications – This study emphasizes the mediating role of financial literacy and identifies the distinct generational drivers of investment intention. Insights support targeted financial education and tailored strategies to engage each generation, including policy initiatives promoting inclusive gold-based financial instruments.Originality – This study offers a generationally segmented perspective on the determinants of investment intention, underscoring diverse financial decision-making processes and providing practical guidance for policymakers, educators, and the investment industry.